Pencegahan Hipertensi Melalui Promosi Kesehatan di Wilayah Kerja Puskesmas Banjarmasin Indah Kota Banjarmasin - Debby Rizalya; M. Bahrul Ilmi; Renate Renate; Chalik Fauzi (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Hypertension is a non-communicable disease which every year has an increasing number of sufferers. Even hypertension cases that occurred in the Banjarmasin Indah Health Center area reached 1161 active cases in 2021. Hypertensive sufferers are often not aware of this disease because the symptoms and complaints are not visible. The implementation of this activity targets people who live in the working area of the Banjarmasin Indah Health Center, which reaches 17,595 people. Implementation of activities starting from February 7 to February 28, 2022, the activities take place according to the service schedule at the Banjarmasin Indah Health Center. Using the direct observation method in the field, the authors found the results that hypertension was the first disease in the 10 most common diseases suffered by the community in 2021. Socialization activities and routine examinations became a mandatory agenda in the implementation of this service. It is known that the root cause of the addition of hypertension comes from the human factor itself. The lack of awareness and knowledge about the dangers of hypertension is one of the reasons. For this reason, an activity plan is made which includes counseling, examination, training of cadres, and additional health workers to prevent and reduce hypertension. The results of this activity have a positive impact. The community becomes aware and understands the prevention and treatment of non-communicable diseases such as hypertension.